Sociability and portraiture from William Hogarth to Thomas Lawrence - Frédéric Ogée (Interfaces)
The period between 1730-1830 saw the rise of an English school of art, much later than the other schools on the European continent. English portrait painters played a crucial part in this evolution by deploying the art of portraiture in infinite variations, in search of a veracity and an intimacy whose contours and peculiarities they tirelessly strove to capture and render. Indeed, they radically transformed their chosen pictorial genre by transcribing onto canvas the new conceptions and perceptions of the individual which had emerged in the Age of Enlightenment. Sensitive to the new universalist values associated with the notions of identity, individuality and sociability, the British portraitists set out to represent the variety and diversity of human beings, moving away from ancient types and models to focus on the particular, singular, circumstantial personalities of the models. In this essay I try to present the narrative of this remarkable blossoming, focussing on the works of a series of exceptional artists—William Hogarth, Joshua Reynolds, Thomas Gainsborough, Thomas Lawrence—whose works provide us with a remarkable visual chronicle of the evolutions of men, women and children in this rich moment in European history.